(untitled) (Biological Sciences - PJSIR, 2010)
For finding a cheap and suitable feed for culture of Ceriodaphnia cornuta studies were carried out for 21 days using chicken manure as fertilizer whereupon C. cornuta population ranged between 50 ± 2 and 10,232 ± 202 Ind./L. (individuals/L). The culture peaked on the 17th day producing the maximum density of 10,232 ± 202 Ind./L. Thus chicken manure can be used as a fertilizer for mass culture of cladocerans, specially C. cornuta.